The effect of food environment on nutrition-related health: evidence from rural China - Lixia Zhang; Shaoting Li; Laiwu Zhang; Weigang Liu (Journal of Health, Population and Nutrition)
Abstract Background Understanding the impact of the food environment on nutrition-related health is essential for addressing the rising prevalence of issues such as overweight and obesity amid rapidly changing dietary patterns in many emerging economies. This study aimed to explore the cause relationship between the food environment, including its three sub-dimensions—food availability, accessibility, and affordability, and nutrition-related health outcomes. Methods This study utilizes survey data collected from rural households in Shaanxi Province, China, in 2022. This analysis utilizes 2SLS and IV-Probit models to analyze the relationship between food environment and nutrition-related health outcomes. Results The findings suggest that the food environment and its sub-dimensions significantly increase nutrition-related health among rural residents. Specially, based on supermarkets and free markets, the food environment has a significant negative impact on BMI and overweight. Besides, food availability and accessibility in rural areas based on supermarkets and free markets significantly increase the nutritional outcomes. To explore the underlying mechanisms, we further analyze the mediating roles of nutrition literacy and dietary quality, the latter of which is evaluated using the Chinese Healthy Eating Index (CHEI) and the Dietary Balance Index (DBI). The results confirm that the food environment positively influences both nutrition literacy and dietary quality. Conclusion Enhancing the food environment is an effective pathway to improving nutrition-related health outcomes in rural China. Policymakers should prioritize dynamic improvements in food availability and accessibility—particularly through supermarkets and farmers’ markets—while also promoting nutrition literacy and diet quality to support long-term public health goals. Graphical abstract Conceptual framework of the relationship between the food environment and nutrition-related health outcomes.